Gut microbial shifts by synbiotic combination of Pediococcus acidilactici and lactulose in weaned piglets challenged with Shiga toxin-producing Escherichia coli - Guevarra, Robin B.; Kim, Eun Sol; Cho, Jin Ho; Song, Minho; Cho, Jae Hyoung; Lee, Jun Hyung; Kim, Hyeri; Kim, Sheena; Keum, Gi Beom; Lee, Chan Ho; Cho, Won Tak; Watthanaphansak, Suphot; et al. (Frontiers in Veterinary Science, 2023)
Development of alternatives to in-feed antibiotics in the swine industry have been the focused of many pig gut microbiota studies to improve animal health. In this study, we evaluated the effects of probiotic Pediococcus acidilactici (PRO), prebiotic lactulose (PRE), and their synbiotic combination (SYN) on weaned pig gut microbiota using 16S rRNA gene sequencing in weaned piglets challenged with Shiga-toxin producing Escherichia coli (STEC). Our data showed that prebiotics, probiotics and synbiotics improved the intestinal health in weaned piglets. No significant differences were observed in species richness and species diversity in weaned piglets fed prebiotics, probiotics and their synbiotic combination. However, beta diversity analysis revealed distinct clustering of the microbiota of according to dietary treatment and by oral challenge of STEC. At the phylum level, Firmicutes to Bacteroidetes ratio was lower in the dietary treatment groups than the control group. Oral supplementation of prebiotics, probiotics and synbiotics enriched the abundance of Prevotella and Roseburia. Succinivibrio was elevated in PRO group; however, Phascolarctobacterium was depleted with STEC challenge regardless of dietary treatment. Overall, our data showed that administration of synbiotics in piglets improved intestinal health through gut microbiota modulation. Our data indicated that prebiotics, probiotics and their synbiotic combination could promote intestinal health through gut microbiota modulation in weaned piglets.